2015
DOI: 10.1159/000438997
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes Induced by Electrical Stimulation of Prelemniscal Radiations for the Treatment of Parkinson Disease

Abstract: Objective: The aim of this work was to study mechanisms of action of electrical stimulation of prelemniscal radiations (Raprl) in the treatment of Parkinson disease, using 2-deoxy-2-fluoro-D-glucose (18F-FDG) Positron Emission Tomography (PET/CT). Materialand Methods: Five patients with PD and predominant unilateral tremor, rigidity and bradykinesia underwent deep brain stimulation (DBS) in contralateral Raprl that improved symptoms from 82.4 to 94.5%. 18F-FDG PET studies were performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…On the other hand, with probabilistic tractography, evidenced in our DWI-MRI studies, we have identified a subset of cerebellar-thalamic fibers ending anteriorly over the ventralis oralis posterior nucleus (Vop), as described in other studies [6] (Fig. 1a), overlapping a fiber component connecting Gp with the thalamus [2, 3]. These fibers have been described in anatomical studies as well; arriving at the thalamus in the thalamic fasciculus [7], the fibers connect the Vop with the supplementary motor area and the dorsolateral frontal cortex.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…On the other hand, with probabilistic tractography, evidenced in our DWI-MRI studies, we have identified a subset of cerebellar-thalamic fibers ending anteriorly over the ventralis oralis posterior nucleus (Vop), as described in other studies [6] (Fig. 1a), overlapping a fiber component connecting Gp with the thalamus [2, 3]. These fibers have been described in anatomical studies as well; arriving at the thalamus in the thalamic fasciculus [7], the fibers connect the Vop with the supplementary motor area and the dorsolateral frontal cortex.…”
Section: Introductionsupporting
confidence: 72%
“…In previous reports, we described the fiber composition of prelemniscal radiations (Raprl) in Parkinson disease (PD) patients [1, 2] and age- and sex-paired controls [3], evaluated through high-angular-resolution diffusion-weighted imaging (DWI) using magnetic resonance imaging (MRI). In the studied cases, 3 fiber components were identified: cerebellar-thalamic-cortical fibers, globus pallidus (Gp)-pedunculopontine fibers, and frontal orbitofrontal cortex-mesencephalic tegmental fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Vim‐PMC fibers may be related to improvement of tremor as revealed by the fact that Vim is a target to treat only tremor, and a recent study relates tremor improvement to the proximity of DBS contacts used for stimulation of cerebellar fibers arriving to this target . The Vop subset may be related to improvement of rigidity as sub‐thalamic and Gpi thalamic fibers project to supplementary motor area and decrease the metabolic activity of this area induced by Gpi‐DBS and Raprl‐DBS correlates with improvement of rigidity. A second component linking Gpi and the dorsal brain stem, in the area of the peduncle‐pontine nucleus (PPN) may be related to improvement of gait.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned before, HFS increases alertness and hyperkinesia when applied to non-specific reticulo-thalamic system, while LFS (8 cps, 450 μs, >5.0 V.) is required to induce cortical synchronization and hipokynesia. Lesions and HFS applied in the white matter fiber bundle between red nucleus and sub thalamic nucleus, within the prelemniscal radiations (Raprl) for the treatment of Parkinson's disease on a white matter fiber bundle connecting mesencephalon with the OFC, reduced hipokynesia ( 47 ) and induce a highly significant decrease in the metabolic activity of OFC in both sides ( 48 ). This white matter fiber bundle has been identified as the superior lateral branch of the middle forebrain bundle (slMFB) and reported effective in controlling TRD and OCD ( 6 ).…”
Section: Introductionmentioning
confidence: 99%